2018
DOI: 10.1007/s00603-018-1553-7
|View full text |Cite|
|
Sign up to set email alerts
|

Computational Verification of the Optimum Boundary Condition of the Brazilian Tensile Test

Abstract: The present research analyses the configuration of jaws to avoid the premature failure of the disc in the Brazilian test. The objective is to depict the loading device configuration that most likely produces results comparable to the Hondros' analytical stress solution. To this end, several numerical analyses have been carried out for different contact angles with the Finite Element Method. It was deduced that the final contact angle plays an important part in the success of the Brazilian test and that the Gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…Failure begins when the equivalent Griffith stress σ G is greater than or equal to the tensile strength σ t of the brittle material. e work performed by Satoh [36], and verified later by others authors [20,37], concludes that the predominant failure condition in this alternative test according to the Griffith criterion is 3σ θ + σ r < 0. erefore, the tensile strength is given by the equivalent Griffith's stress [8]:…”
Section: New Analytical Expression For the Brazilian Test With Loadinsupporting
confidence: 55%
See 1 more Smart Citation
“…Failure begins when the equivalent Griffith stress σ G is greater than or equal to the tensile strength σ t of the brittle material. e work performed by Satoh [36], and verified later by others authors [20,37], concludes that the predominant failure condition in this alternative test according to the Griffith criterion is 3σ θ + σ r < 0. erefore, the tensile strength is given by the equivalent Griffith's stress [8]:…”
Section: New Analytical Expression For the Brazilian Test With Loadinsupporting
confidence: 55%
“…e fact that the stress field at the centre of the disk is quite insensitive to the loading pressure distribution does not guarantee the validity of the results obtained from a statistical point of view. A recent research work indicated that the distribution of the contact load is not uniform and that the statistical validity of the prediction, based on the Hondros assumption [17], depends on the loading arc length [20]. e models developed in the engineering field usually intend to reproduce the case under study with the required accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…7 The range of contact angles recommended by the ISRM 11 does not seem to meet the Griffith's criterion, as it has been demonstrated that the failure, for these angles, can be located near the loading zone. 7,[14][15][16] This would invalidate the test for the determination of the tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…The classic Brazilian disk test determines the tensile strength of brittle materials by diametrically loading a thin circular disk to failure. The test has become a standard method of determining the tensile strength of brittle rock by the International Society of Rock Mechanics (ISRM) and the American Society for Testing and Materials (ASTM) (Guti errez-Moizant et al, 2018). Hondros (1959) derived the full stress field for a diametrically loaded Brazilian disk under plane stress conditions.…”
Section: The Confined Brazilian Disk Testmentioning
confidence: 99%